DISPOSITION ANALYSIS OF ELEMENTARY SCHOOL STUDENTS IN MATHEMATICAL PROBLEM SOLVING - Riandi Marisa; Yulia Santi; Ety Mukhlesi Yeni; Sri Dewi Nirmala (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The role of students' attitudes (disposition) towards mathematics is an important element in solving mathematical problems and must be maximized properly. Disposition has the following indicators: self-confident, flexibility, persistent, curiosity, reflecting, apply it. This study aims to describe the elementary students' mathematical disposition profile towards problem solving abilities. The research method uses qualitative-descriptive. Data were collected through questionnaires, observations, and interviews then analyzed by triangulation technique. The results show that there is a significant relationship between elementary school students' mathematical dispositions to problem solving abilities. Students who meet the "excellent" category of mathematical disposition indicators (mathematical disposition indicators score > 85%) have good problem solving skills. Furthermore, students who are categorized as "less" (mathematical disposition indicators score < 60%) have problem solving abilities that need treatment. Each indicator description is described in this article.